Analisis Pemahaman Siswa Tentang Perlindungan Konsumen Terhadap Kepercayaan Pembelian Barang di Shopee - Qurrotul A’yuni; Rohmatul Nazila Ramadhani; Yasmin Yasmin; Firza Agung Prakoso (Jurnal Manajemen Bisnis Era Digital, 2025)
This research aims to analyze students' understanding of consumer protection and its influence on confidence in purchasing goods on Shopee. The research used a qualitative approach with in-depth interview methods with high school students in Pasuruan. The research results show that students' shopping frequency at Shopee varies, with a fairly high level of satisfaction although there are still doubts about the effectiveness of the consumer protection features. Most students understand consumer rights and obligations as well as procedures for filing complaints, but some students feel the need for further education regarding steps to handle fraud. Product information on Shopee is considered accurate and buyer reviews provide additional confidence, but the implementation of consumer protection is considered not optimal. In conclusion, students' understanding of consumer protection contributes positively to their confidence in making purchases, but there is a need for improvement in education and transparency of protection features. It is hoped that the implications of this research will become a reference for e-commerce, schools and the government in increasing consumer awareness and protection in the digital era.